A study on fuel additive of methanol for room temperature direct methanol fuel cells. (15th July 2018) - Wang, Meng; Chen, Ming; Yang, Zhaoyi; Wang, Yituo; Wang, Yingrui; Liu, Guicheng; Lee, Joong Kee; Wang, Xindong
Graphical abstract: Hydrogen peroxide is used as a pro-oxygenic agent for methanol electro-oxidation to direct methanol fuel cell, which can eliminate the adverse impact of COads and improve the performance of the cell obviously. Highlights: Hydrogen peroxide as an additive is introduced into anode for direct methanol fuel cells. Effect of hydrogen peroxide with different concentrations on fuel cell performance is discussed. Influence of hydrogen peroxide additive on anodic and catholic reactions is revealed. Nyquist, cyclic voltammetry and polarization curves are used to analyze mechanism. Fuel cell performance is promoted by 34.1% with addition of 0.1 mol·L −1 hydrogen peroxide at 25 °C. Abstract: Hydrogen peroxide is added into the anode methanol fuel as a pro-oxygenic agent to improve the electro-oxidation reaction rate of methanol in low-temperature direct methanol fuel cell. Cyclic voltammetry, electrochemical impedance spectroscopy and steady-state polarization with three-electrode system are used to test the catalytic efficiency with different concentrations of hydrogen peroxide additive. The mechanism of pro-oxygenic activity is revealed by cyclic voltammetry method. The results of electrochemical analysis show that the peak current density and peak power density are the highest when the concentration of hydrogen peroxide additive is 0.1 M at room temperature, increase 12.2% and 34.1% than those of pure methanol solution, respectively. The anode charge transfer resistances reduce gradually as the concentrations of hydrogen peroxide increase from 0 to 0.3 M. The tests under different temperature indicate that the promotion effect of hydrogen peroxide additive is significant at room temperature rather than at high temperature. The results show that hydrogen peroxide can be an effective pro-oxygenic agent for methanol electro-oxidation to improve the anode methanol electro-oxidation reaction of direct methanol fuel cell at room temperature.